Cinética de la inmunoglobulina-A salival (IgAs) en adultos jóvenes con capacidad aeróbica promedio o excelente antes y después de una prueba de esfuerzo máximo - Ochoa Martínez, Paulina Yesica (2017)
Background: Aim: To compare the concentration of secretory immunoglobulin-A (sIgA) in young adults with average or excellent aerobic capacity before and after a cardiopulmonary graded exercise test. Methods: Participants were nine apparently healthy physically active males (Mean age = 21.3 ± 2.1 yr.), randomly allocated in two groups based on their VO2max: a) average aerobic capacity (AEC, n = 5) or b) excellent aerobic capacity (EAC, n = 4). Participants performed the Bruce protocol to determine their aerobic capacity. The sIgA was measured before the test, immediately after the test and 60-, 120-, 240-, and 1440-min after the test. Results: Mixed factorial 2 x 6 ANOVA indicated no significant interactions between groups and measurements (p = 0.956), and main effect groups on sIgA (AEC = 85.4 ± 19.3 μg/mL vs. EAC = 79.2 ± 21.5 μg/mL, p = 0.836). Tukey’s post hoc analysis revealed significant differences measurement obtained immediately after the test and between the initial measurement (p = 0.020), 60-min (p = 0.030), 240-min (p = 0.016), and 1440-min (p = 0.028) following the test. Conclusion: There is no change in sIgA kinetics depending on the aerobic capacity of the participants following an aerobic capacity cardiopulmonary graded exercise test.